Exploring the Roles of Tax Morale, Religiosity, and Nationalism in Tax Compliance with the Moderating Effect of Accounting Literacy - Natasya Putri Rahmalia; Siti Rismaya; Diana Sari; Sharina Osman (Universitas Pendidikan Ganesha, 2024)
Despite increased understanding of factors influencing tax compliance, such as tax morale, religiosity, and nationalism, significant gaps remain in how these factors, when moderated by accounting literacy, translate into actual compliance rates. This study investigates whether tax morale, religiosity, and nationalism impact tax compliance behaviors among corporate taxpayers, using accounting literacy as a moderating variable at the West Java I Directorate General of Taxes Regional Office. Employing quantitative methods, the research analyzes data from 100 corporate taxpayers registered at this office, using probability sampling and SEM-PLS analysis via the SmartPLS application. Results indicate that while tax morale and nationalism significantly affect tax compliance behavior, religiosity does not. Furthermore, increased religious understanding may sometimes lead to reduced compliance, as it can prioritize spiritual over civic obligations. Contrary to expectations, accounting literacy does not moderate the effects of tax morale, religiosity, or nationalism on compliance. This suggests that factors other than financial knowledge play critical roles in determining tax compliance.